2015
DOI: 10.1163/1937240x-00002304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biofloc on the survival and growth of the postlarvae of three penaeids (Litopenaeus vannamei, Fenneropenaeus chinensis, and Marsupenaeus japonicus) and their biofloc feeding efficiencies, as related to the morphological structure of the third maxilliped

Abstract: A B S T R A C TBioflocs contribute to the nutrition and growth of some penaeid shrimp, such as L. vannamei, by providing an additional food source in intensive, limited exchange production systems. However, it remains unclear whether other penaeids could use bioflocs as food sources. Furthermore, little is known concerning the feeding mechanism of shrimp for harvesting and consuming bioflocs. This study determines whether three penaeid species could use bioflocs as food sources and suggests mechanical function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…Significant effects of bioflocs on the growth, immune and antioxidant response of other commercially important farmed species, including black tiger (P. monodon) (Anand et al 2014(Anand et al , 2017Kumar et al 2017) and L. stylirostris (Cardona et al 2016) have also been documented. Similar results were also reported in freshwater prawn (Macrobrachium rosenbergii) (Miao et al 2017) and Chinese shrimp (F. chinensis) (Kim et al 2015) where augmentation of biofloc medium with Bacillus improved immune response and reduced oxidative stress.…”
Section: Antioxidant Effectssupporting
confidence: 84%
See 2 more Smart Citations
“…Significant effects of bioflocs on the growth, immune and antioxidant response of other commercially important farmed species, including black tiger (P. monodon) (Anand et al 2014(Anand et al , 2017Kumar et al 2017) and L. stylirostris (Cardona et al 2016) have also been documented. Similar results were also reported in freshwater prawn (Macrobrachium rosenbergii) (Miao et al 2017) and Chinese shrimp (F. chinensis) (Kim et al 2015) where augmentation of biofloc medium with Bacillus improved immune response and reduced oxidative stress.…”
Section: Antioxidant Effectssupporting
confidence: 84%
“…The effects of bioflocs on larval performance may depend on shrimp species. For example, Kim et al (2015) evaluated the effects of bioflocs as natural food sources for the postlarvae (PL10-PL20) of three Penaeid species (L. vannamei, F. chinensis and M. japonicus), in the presence or absence of supplemental feeds (45% cp). The presence of both biofloc and feeds resulted in better growth rate of L. vannamei PL than in biofloc-based treatment, whereas the growth and survival rates of the other two species were not affected by dietary treatments.…”
Section: Larval Stagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al . () compared efficiency of biofloc‐culture for postlarvae of three penaeid species ( L. vannamei , Fenneropenaeus chinensis and Marsupenaeus japonicus ) and related this to the morphological structure of the third maxilliped. Results indicated that L. vannamei postlarvae may have higher filter‐feeding capacity, and therefore nutritionally benefit more from the bioflocs, compared with the other two species.…”
Section: Bacteria As Food In Aquaculturementioning
confidence: 99%
“…The heart is a vital organ for cardiovascular circulation in shrimp. Cardiovascular dysfunction has been used to evaluate environmental toxicants as significant risk factors in crustaceans [ 34 , 35 ]. The maxilliped is one of the three pairs of appendages located immediately behind the maxillae of shrimp and plays multiple functions on feeding and facilitating oxygen uptake [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%